The Influence of Principal’s Leadership, Work Culture and Work Commitment on Teacher’s Professionalism - Sari, Intan Mayang; Fitria, Happy; Wahidy, Achmad (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2024)
This study aims to examine 1) the influence of principal leadership on teacher professionalism 2) the effect of work culture on teacher professionalism 3) the effect of organizational commitment on teacher professionalism 4). the influence of principal leadership, work culture, and organizational commitment to teacher professionalism. This study uses quantitative methods as a research method. This study shows that 1) principal leadership has no partial and insignificant effect on teacher professionalism with a value of t count <of t table or 1.972<1.9908 2) there is an effect that work culture has a partial and significant effect on teacher professionalism with the value of t count> from t table or 5,319> 1,988. 3) work commitment has a partial and significant effect on teacher professionalism with a value of t count> t table or 2.656. > 1,988. 4) there is an influence of leadership, work culture, and work commitment that have a simultaneous and significant effect on teacher professionalism with a value of f count> t table or 2.656. > 2.71.